Biosorption of Lead Ions on Biosorbent Prepared from Plumb Shells (Spondias mombin): Kinetics and Equilibrium Studies: Biosorbent Prepared from Spondias mombin - Adeogun, Abideen Idowu; Bello, Olugbenga Solomon; Adeboye, Mariam Dasola (Biological Sciences - PJSIR, 2010)
Plumb shell was used to prepare an adsorbent for biosorption of lead ions in aqueous solution at 25 °C. The adsorption capacity of the adsorbent at equilibrium was found to increase from 2.8 to 49.0 mg/g with an increase in the initial lead ion concentration from 50 to 200 mg/L. Using the equilibrium and kinetics studies, isotherm of the lead ions on the biosorbent was determined and correlated with common isotherm equations. The equilibrium data for lead ion adsorption fitted well into the Freundlich equation, with a value of 0.76 (R2 = 0.9), with distribution coefficient of 4.90. The biosorption of lead ions on the adsorbent from plumb shells could best be described by the pseudo-second-order equation. The kinetic parameters of this best-fit model were calculated and discussed.